REKONSTRUKSI PEMBERI GRATIFIKASI SEBAGAI SUBYEK TINDAK PIDANA KORUPSI - Sulastri, Lusia; Tri Wibowo, Kurniawan (IBLAM LAW REVIEW, 2021)
Gratification has not yet been regulated by laws and regulations as a criminal act. This happened in the Samin Tan case, where the judges of the Jakarta Corruption Court released Samin Tan from granting a gratuity of IDR 5 billion to Eni Maulani Saragih as a member of Commission VII DPR for the 2014-2019 period. The current formulation of policies regarding gratification in Law Number 31 of 1999 concerning Corruption requires restructuring, especially in the substance of the meaning of gratification, reporting on receipt of gratification to the KPK, criminal sanctions, and qualifications of the giver and recipient of gratification. so that the optimization of the application and enforcement of appropriate laws is achieved, namely certainty and justice. Reconstruction of the gratification provider for corruption must be based on a low level of gratification and bribery according to its definition. Bribery has the definition of a relationship due to the consequences of actions that result in or influence a person in his position as a state administrator to the interests of the bribe giver. While gratification should only be a gift, without having to be associated with any reciprocal actions. With a clear distinction between bribery and pure gratification that does not lead to bribery, the weight of the punishment is determined. Likewise, the gratuity giver, if it is said to be a bribe, must explain how much punishment was given to him. For example, the giver of gratuities as referred to in Article 12 B of Law no. 31 of 1999 as amended by Law no. 20 of 2001 concerning the Eradication of Corruption Crimes is the same as receiving gratuities. Thus the effect can be felt in a balanced way because it destroys requests and requests for prohibited acts.